PENYULUHAN DIGITAL MARKETING UNTUK USAHA RUMAHAN - Anisatul Munawaroh; Hasmawati (AbdiMasya | Hira Institute, 2023)
Sinar Gading Village has potential, especially for home-based businesses that have not been optimally managed. This is caused and illustrated by the intellectual level of the community with education below junior high school and the majority of the population of Sinar Gading village work as laborers and some residents have home businesses such as oven craftsmen, kemplang makers, crackers and tofu makers. In improving their business, Sinar Gading residents do not yet have knowledge related to digital-based sales. Therefore, the purpose of this service is to provide counseling about Digital Marketing for home businesses in the Sinar Gading village, Tabir Selatan District. The method used in this training activity is the lecture and discussion method. The lecture method is used by the presenters to explain material related to cooperative financial management materials. This was followed by a discussion to deepen the material, both in the form of individual questions and answers and representatives of participants. The results of the service showed very high enthusiasm from the participants who were home-based business actors in the Sinar Gading ungai Putih village. This was shown by the many questions asked by participants regarding the procedure for creating accounts on the market place platform and the resource persons trying to answer these questions and provide in-depth explanations of the topics asked.